Analysis of the Thai banking crisis. - Chew, Alvin Siong Yew. (2008)
This research project represents a contribution to the growing body of knowledge on the Asian banking crisis. Its objective is to provide an in-depth analytical study of the Thai banking crisis which lies at the core of Thailand’s economic slump. It is hoped that the study will provide fresh insights into the Thai banking crisis and serve as a useful reference for future research in this area.